2018
DOI: 10.1155/2018/1629147
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Internet Use—An Important Comorbidity in Child and Adolescent Psychiatry: Prevalence and Correlation Patterns in a Naturalistic Sample of Adolescent Inpatients

Abstract: Background Few studies have examined the prevalence of problematic internet use (PIU) in young people undergoing inpatient treatment in child and adolescent psychiatry centers. The aims of our study were thus (a) to assess the frequency of comorbid PIU in a sample of adolescent psychiatric inpatients and compare it with a control group of nonreferred adolescents and (b) to gain insights into correlations between PIU and psychiatric comorbidities. Methods 111 child and adolescent psychiatry inpatients (CAP-IP, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 60 publications
2
27
0
2
Order By: Relevance
“…According to the report of UNESCO [28], one-third of the children and adolescents worldwide had been bullied, while 5%-21% of the children and adolescents had been experienced cyberbullying. Previous studies found that peer bullying was significantly associated with IGD among college students [29] and pathological Internet use among adolescents [30]. Online bullying has also been anecdotally and empirically linked to multiple maladaptive emotional and behavioral outcomes among adolescents, such as depression, substance use, and suicide [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…According to the report of UNESCO [28], one-third of the children and adolescents worldwide had been bullied, while 5%-21% of the children and adolescents had been experienced cyberbullying. Previous studies found that peer bullying was significantly associated with IGD among college students [29] and pathological Internet use among adolescents [30]. Online bullying has also been anecdotally and empirically linked to multiple maladaptive emotional and behavioral outcomes among adolescents, such as depression, substance use, and suicide [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] A growing number of studies have found an association between high levels of internet use in young people and poor mental health, including depression, anxiety, attention deficit hyperactivity disorder, hostility/aggression, suicidal ideation, and self-harm. [3,[8][9][10][11][12][13][14][15][16] However, most existing research is based on cross-sectional data and so the temporal relationship between mental health problems and internet use is currently unclear. The lack of longitudinal studies assessing the consequences of screen-based activities was recently highlighted as a key limitation in the field.…”
Section: Introductionmentioning
confidence: 99%
“…It is characterized by symptoms including: (1) need for extending online time (tolerance), (2) withdrawal symptoms, (3) inadequate control on Internet use, (4) continuation of Internet use disregarding to problem awareness, (5) excessive online time, (6) negative consequences [5,6]. A bunch of terms were used in literature to describe this condition, such as Pathological Internet Use [7], Internet Abuse [8], Internet Use Disorder, Problematic Internet Use [9] and etc. In the third section of the Fifth Edition of Diagnostic and Statistical Manual of Mental Disorders (DSM-5) [10], which proposed conditions for future study, Internet Gaming Disorder is included as a potential diagnosis for further discussion.…”
Section: Introductionmentioning
confidence: 99%